How does Marvel Cinematic Universe (MCU) imply the counseling practice? - Haryadi, Rudi; Farial, Farial; Sanjaya, Sanjaya (ProGCouns: Journal of Professionals in Guidance and Counseling, 2022)
The Marvel Cinematic Universe (MCU) is a major franchise in the Hollywood film industry that tells the story of various superheroes in one story continuity. The popularity of the MCU has skyrocketed in society for 14 years ago and has influenced the development of popular culture today. This paper aims to review the potential of the MCU as one of the big trends in the millennial era in the practice of cinema counseling. The review method used is a literature study, the author reviews various related literature to present a comprehensive discussion. The results of the review suggest that the MCU has great potential to be utilized in cinema counseling, especially for millennial children and teenagers. This is because in essence film is a medium that has been tested to be effectively used to shape, reconstruct, and change the mindset of individuals. In addition, the MCU as a group of superhero films also inserts various moral messages and life lessons that can be abstracted, and used as a metaphor by counselors in the practice of cinema counseling. However, more research is still needed regarding the use of MCU in cinema counseling to become a solid foundation for counselors to practice it.